The Challenges of Fiscal Consolidation and Debt Reduction in the Caribbean - Yartey, Charles Amo.; Chiedu Okwuokei, Joel.; Narita, Machiko; Nicholls, Shelton (Washington, D.C. : International Monetary Fund, 2012)
This paper examines debt dynamics in the Caribbean and discusses policy options for reducing the high debt levels. Based on empirical studies of factors underlying global large debt reduction episodes, important policy lessons are drawn for the Caribbean. The analysis shows that major debt reductions are associated with strong growth and decisive and lasting fiscal consolidation efforts. Since growth in the current environment is virtually nonexistent, significant fiscal consolidation is inevitable in the region. Better control of the public wage bill, increasing public sector efficiency and tackling transfers are the obvious targets to reduce spending. On the revenue side, there is ample room to reduce tax expenditures, eliminate distortions while broadening the tax base. Fiscal consolidation needs to be complemented by a comprehensive debt reduction strategy including tax policy reforms and structural reforms to boost competiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet